Effect of synbiotic plus selenium or betaine on performance, intestinal health, nutrient digestibility, and carcass quality of Tegal ducks - I. Mangisah; S. Sugiharto (Journal of the Indonesian Tropical Animal Agriculture, 2023)
This study aimed to examine the effect of synbiotics and synbiotics plus Selenium or betaine on the performance, intestinal ecology, nutrient digestibility, and carcass quality of Tegal ducks. A total of 200 ducks were randomly assigned to one of four treatments in a completely randomized study. The treatment groups included control (basal feed without any additive), synbiotics (Syn; basal feed supple-mented with 2% synbiotics), synbiotic plus selenium (Syn+Se; basal feed supplemented with 2% syn-biotics and 10 mg/kg selenium), synbiotic plus betaine (Syn+Bet; basal feed supplemented with 2% synbiotics and 500 mg/kg betaine). The Tegal duck performance, intestinal health, nutrient digestibil-ity, and carcass quality were determined at the end of the study. Final body weight and feed conversion ratio (FCR) were improved (p<0.05) in ducks given synbiotic plus selenium compared to other treat-ments. Betaine or selenium in combination with synbiotics lowered (p<0.05) the caecum’s pH values. Synbiotic plus selenium or betaine enhanced (p<0.05) the numbers of lactic acid bacteria (LAB), but did not reduce the colonies of Escherichia coli in the caecum of ducks. Crude protein and crude fiber digestibility in Tegal ducks were considerably (p<0.05) improved by the administration of synbiotics, synbiotics plus selenium, or synbiotics plus betaine as compared to control. The Syn+Bet treatment, in contrast to the Syn and Syn+Se treatments, substantially (p<0.05) enhanced N and Ca retention. The Syn+Se and Syn+Bet groups had higher (p<0.05) carcass and thigh proportions than the control and Syn groups. The Syn+Se and Syn+Bet groups had higher (p<0.05) meat weights than the control and Syn groups. The treatment groups had less (p<0.05) abdominal fat than the control. Total cholesterol of meats was lower (p<0.05) in ducks treated with synbiotics or a combination of synbiotics with seleni-um or betaine. In conclusion, dietary administration of synbiotic plus selenium resulted in improved body weight, FCR, intestinal ecology, nutrient digestibility, carcass traits, meat weight and total cho-lesterol in meats of Tegal ducks.